To Be, or not to Be: Unionists and Bektashis in the Second Constitutional Era (1908-1918) (Journal of Alevism-Bektashism Studies, 2019)
Together with the Janissary Massacre in 1826, the Bektashi dervish lodge, that was seen in liaison with the Janissaries and, moreover, was alleged to have incited them, was wanted to be disbanded and the traditional belief of the lodge was wanted to be converted. In 1826 and in the following years, some religious leaders of the lodge were executed, some religious leaders were exiled, a significant amount of property was confiscated, and Sunni religious leaders were appointed to the head of some lodges. The policy of Sunization and disbanding of the Bektashi lodge continued throughout the 19th century, and this policy, started in 1826, was consistently applied in the Tanzimat Reform Era and during the period of Sultan Abdulhamid II. Bektashis resisted the policy of disbanding and Sunnization, strived to keep their beliefs and rituals alive, and tried to protect their lodge and religious leaders. The autocracy which was constituted by the regime of Sultan Abdulhamid II and lasted for decades, has finally ended with the Second Constitutional Era. The Liberty was welcomed with joy by Bektashis. That year Bektashis entertained hope that they reached the Liberty, demanded in various ways from the constitutional government to finally recognize their identity, wrote petitions, and demanded that their religious leaders be appointed as heads of the lodges. This paper analyses the relation between Bektashis and the governments in the constitutional years and the government of Union and Progress during the Second Constitutional Era, and focuses on the expectations of Bektashis from the Liberty, their search for recognition of their identities, in other words the process of being, or not being, within legal limits. The paper focuses on the period when the Unionists were, first, in control and, then, in full power. It analyses the Bektashi politics that the Unionist power continued between 1908-1918 until the First World War and realized during the First World War, and the Bektashis’ expectations from this politic and their reactions. The paper also analyses the Bektashi researches, that started with Baha Sait in the governmental period of the Union and Progress and then reached an important stage with Mehmet Fuad, and tries to evaluate the relation between these studies and the nationalism brought up by the Union and Progress together with the reaction of the Bektashis.